2016
DOI: 10.1016/j.vhri.2015.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Utilities for Type 2 Diabetes Treatment-Related Attributes in a South Korean and Taiwanese Population

Abstract: Utilities associated with type 2 diabetes medication-related attributes were elicited from a general population sample from South Korea and Taiwan. Treatment-related attributes, in particular dose frequency and nausea, had a measurable effect on utility and should be considered when selecting treatment regimens for South Korean or Taiwanese patients with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…The prevalence of diabetes has also increased from around nine to 11% between 2011 and 2013 in South Korea, which is alarming because diabetes and its related complications often increase the burden individuals and health care systems experience in terms of health outcomes and costs [2, 3]. In fact, previous studies have reported that diabetes act to decrease the health-related quality of life (HRQoL) of affected individuals [4]. Furthermore, diabetes and its related complications are a leading cause of morbidity and mortality in Korea [5].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of diabetes has also increased from around nine to 11% between 2011 and 2013 in South Korea, which is alarming because diabetes and its related complications often increase the burden individuals and health care systems experience in terms of health outcomes and costs [2, 3]. In fact, previous studies have reported that diabetes act to decrease the health-related quality of life (HRQoL) of affected individuals [4]. Furthermore, diabetes and its related complications are a leading cause of morbidity and mortality in Korea [5].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, a total of 39 presented findings exclusively related to acute or long-term diabetes-related complications, 15 presented findings exclusively related to the influence of treatment-related attributes on QoL and 15 captured findings on both complications and treatment attributes. Therefore, a total of 30 articles presented utility/disutility values associated with treatment-related attributes or process characteristics ( Table 1 ) 7–36 These included a total of fifteen conducted in Europe, 9–11 , 13–15 , 19–21 , 24 , 25 , 29 , 31 , 33 , 34 eight conducted in Asia, 12 , 17 , 18 , 23 , 27 , 28 , 32 , 35 two in North America, 16 , 36 one in Latin America, 30 one in the Middle East, 8 one in Africa, 7 and two were multinational or the setting was not stated. 22 , 26 Most studies were conducted in people with T2D although three were conducted in general population samples 24 , 28 , 33 and one included both general population groups and groups with T2D.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a total of 30 articles presented utility/disutility values associated with treatment-related attributes or process characteristics ( Table 1 ) 7–36 These included a total of fifteen conducted in Europe, 9–11 , 13–15 , 19–21 , 24 , 25 , 29 , 31 , 33 , 34 eight conducted in Asia, 12 , 17 , 18 , 23 , 27 , 28 , 32 , 35 two in North America, 16 , 36 one in Latin America, 30 one in the Middle East, 8 one in Africa, 7 and two were multinational or the setting was not stated. 22 , 26 Most studies were conducted in people with T2D although three were conducted in general population samples 24 , 28 , 33 and one included both general population groups and groups with T2D. 29 The most frequently used elicitation method was the EQ-5D (3L or 5L), which was used in fourteen studies, 8 , 12–15 , 18 , 22 , 23 , 25 , 27 , 30 , 32 , 34 , 36 followed by TTO methodology used in ten studies, 10 , 11 , 16 , 19–21 , 24 , 26 , 29 , 33 then the Short Form 6 Dimensions questionnaire (SF-6D; three studies), 15 , 31 , 35 SG (three studies), 9 , 17 , 28 Health Utilities Index-...…”
Section: Resultsmentioning
confidence: 99%
“…[45][46][47][48] These "process utilities" quantify the impact of attributes such as mode of administration, dose frequency, medical device attributes, and aspects of treatment convenience that may have an impact on patients' quality of life. 16,17,23,[49][50][51][52][53][54][55][56][57] Treatment process usually has less impact on utility than efficacy, safety, or symptom severity, 43 but it is often important to patients. Furthermore, treatment process could affect treatment adherence, which can influence outcomes.…”
Section: Treatment Process Utilitiesmentioning
confidence: 99%